Shell game / 5 - Pearson, Ridley (Kingdom Keepers, 2013)
The Kingdom Keepers have their hands full when, during the inaugural cruise of the Disney ship, Fantasy, to exotic locations, they discover that the Overtakers have infiltrated the cast, stolen a journal that belonged to Walt Disney himself, and plan to unleash a powerful evil, the Chernabog.